Analyzing a problem-solution pattern in the transcription of a conversation: suggestions for the EFL classroom - César Alberto Navas Brenes (Actualidades Investigativas en Educación)
This paper analyzes a problem-solution pattern shown in the transcription of a conversation.  This analysis is based on a conversation that has been elicited from three native speakers of English.  These speakers were given a topic that dealt with the problem of children being constantly exposed to violent video games.  As a result, the writer recorded an oral text that contains several elements related to a problem-solution pattern such as the main issue, opinions, personal examples, possible solutions, and the evaluation of these solutions.  The writer analyzed this pattern in terms of discourse analysis using idea units from the transcription.  Moreover, the writer will point out how appropriate this transcription is for preparing teaching tasks for the EFL classroom.